Cyberbullying In Elementary School Students: Should There Be An Anti Bullying Community? - Muhammad Indra; Jasiah, Jasiah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
In the current digital era, the phenomenon of cyberbullying has become a major concern in the educational context, especially among elementary school children. This qualitative research aims to explore the impact of cyberbullying on elementary school children. Through data analysis from in-depth interviews with teachers, principals and students, the researcher was able to identify various impacts felt by victims of cyberbullying, including psychological disorders, decreased academic achievement, and social isolation. The research method used in this study is qualitative with an analytical descriptive approach and an empirical normative approach. This research was conducted in Parenggean Sub-district, East Kotawaringin Regency. The research location was chosen to describe a more typical context in research on cyberbullying in elementary school students, the location was chosen because of the availability of data and accessibility that facilitates the collection of relevant information. Data analysis in this study was conducted inductively. The steps of data analysis will include coding the data, categorizing the findings, identifying patterns, and developing major themes. Data validity was checked through triangulation. The results show that bullying occurs in the form of: physical, verbal, relational, and electronic, the cause of bullying is because children get excessive punishment, parents' neglectful attitude towards children, the influence of the surrounding environment where they live and children's habits of watching both on television, gadgets see indecent content and are practiced on their friends so that bullying occurs. As a result of bullying, elementary school students who are victims of cyberbullying tend to have difficulty coping with the stress and anxiety resulting from the experience. The role of teachers, parents, friends in supporting cyberbullying victims to face and overcome the negative impacts. These findings provide a deeper understanding of the complexity of the phenomenon of cyberbullying in elementary school children and its implications for educational practice.